Effects of Amino Acid Decarboxylase Genes and pH on the Amine Formation of Enteric Bacteria From Chinese Traditional Fermented Fish (Suan Yu) - Yang, Qin; Meng, Ju; Zhang, Wei; Liu, Lu; He, Laping; Deng, Li; Zeng, Xuefeng; Ye, Chun (Frontiers in Microbiology, 2020)
The formation of biogenic amines (BAs) is an important potential risk in Suan yu. This study investigated the amine production abilities of 97 strains of enteric bacteria screened from Suan yu. The genotypic diversity of amino acid decarboxylase and the effect of pH were explored on 27 strains of high-yield BAs. Results showed that high levels of putrescine, histamine, and cadaverine were produced by the 97 strains. In addition, 27 strains carried odc, speA, speB, adiA, and ldc genes. Thirteen carried hdc gene. Morganella morganii 42C2 produced the highest putrescine content of 880 mg/L via the ornithine decarboxylase pathway. The highest histamine content was produced by Klebsiella aerogenes 13C2 (1,869 mg/L). The highest cadaverine content was shown by Klebsiella pneumoniae 47C2 (1,821 mg/L). odc, adiA, speB, ldc, and hdc play important roles in the cellular acid stress response. Acid stress caused the growth delay but can increase the contents of putrescine, histamine, and cadaverine. Decarboxylase was strain specific rather than species specific. This study provides a reference for the genotypic diversity of decarboxylase and effect of pH on the types and abilities of BAs produced by enteric bacteria in Suan yu.